Editor’s foreword to the first issue of "Libellarium" (Libellarium: journal for research in the field of information and related sciences, 2022)
Among many literary terms found in the Lexicon Latinum (1742) by Andrija Jambrešić and Franjo Sušnik (auctor and scriptor — book writer; impressio — printing; libellus — booklet; typographeum — print house; typographia — to know how to set and print letters etc.) we can also find the term libellarium — bookcase, bookshelf, for keeping different letters and papers. This descriptive definition of libellarium sums up all the three areas this journal is dedicated to — the history of the writting, the history of books, and the history of memory institutions, which is the reason why this term was selected as the name of the journal.The main aims of Libellarium are motivating and promoting the research of the history of the written word, books and heritage institutions. The Croatian written and printed heritage offers infinite possibilities of research using the most current research methodology, which has not been applied in earlier research. The editorial board of Libellarium therefore invites research papers that will throw more light on the Croatian written and printed heritage, as well as papers that will promote research in line with the prevailing and the most current research paradigms. Such a blend of source and methodology is supposed to improve research methods, increase the interest in investigating the history of the written word, books and heritage institutions, and eventually result in their establishment as modern scientific disciplines in Croatian scholarship.This especially refers to the history of books, which has, in the past 50 years (starting with the pioneering book by Lucien Febvre and Henri-Jean Martin L’Apparition du livre published in 1958) evolved as a discrete scientific discipline with a developed research methodology that leans on the achievements of the history of literature, history in the narrow sense, cultural anthropology, sociology, librarianship, and many other sciences. There is only a handful of research papers from Croatia published in the past few years which follow, but also critically examine, the authors such as Robert Darnton, Roger Chartier, Paul Saenger, and other prominent scholars, as the modern research methodology has still not been sufficiently applied in humanities and social sciences research in Croatia. The editorial board of Libellarium wishes, on the one hand, to motivate modern research such as the interaction between the book and the reader, preparation of the manuscript or the printed text for the reader, appropriation methods, etc., and on the other, motivate the examination of the whole corpus of original sources for the history of (especially Croatian) books, as well as the interplay of social, cultural, intelectual, economic, legal and political circumstances that provided the conditions for the production, distribution and appropriation of texts, i.e. work that would establish firm foundations for future research.In line with this orientation, the first issue of Libellarium brings papers devoted to two issues. The papers by Aleksandar Stipčević, Željko Vegh and Slavko Harni present some of the possible sources for the history of books: private library inventories, records of canonical visitations and bibliographies. The papers by Jelena Lakuš, Maja Krtalić, Zorka Renić and Tatjana Kreštan examine the social circumstances of reading, librarianship and periodical publishing: preconditions for reading in Dalmatian reading societies in the early 19th century, the possibilities of publishers’ advertisements in newspapers from Osijek in the late 19th century, and the context of publishing local weekly journal (Tjednik bjelovarsko-križevački) in the late 19th and early 20th century. The paper by Andy White on the modern digital environment and the return of the age-old idea of a universal library may seem to be different from the two prevailing strands in other papers in this issue, but it also focuses on the examination of the general social and technological framework that accentuates this idea in certain historical periods.In addition to publishing research papers, Libellarium will also publish reprints of sources for the history of books. In this issue, following the paper by Slavko Harni, we bring the bibliography Književnost bosanska by Ivan Franjo Jukić.Finally, following the tradition of research journals, Libellarium will also publish reviews of important works on the history of the written word, books and heritage institutions.